Stimulating lecturers' innovative behaviour in Malaysian polytechnics. - Raja Hussin, Tengku Ahmad Badrul Shah; Abd. Ghani, Nik Azida; Jusoff, Kamaruzaman (Academic Leadership, 2009)
The article presents a study for stimulating lecturers' innovative behaviour in Malaysian polytechnics. In the study, a total of 272 lecturers from two polytechnics have been selected as respondents using multi-stage sampling method. The profile of the respondents was based on gender, highest academic achievement, teaching experience and teaching experience in polytechnic.